KEMAMPUAN MEMBACA PEMAHAMAN MENGGUANAKAN MODEL KONSTRUKTIVISME PADA SISWA KELAS VIII MTS DARUL HIKMAH PEKANBARU - Sukmawati Sukmawati; Auzar Auzar; Dudung Burhanudin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: This article aims to find out the category of reading comprehension for classVIII students of MTS Darul Hikmah Pekanbaru. And also apply a constructivismapproach in learning reading comprehension. This research was conducted in aqualitative descriptive manner with the collection of observational data anddocumentation. This type of research is a qualitative research with inferential statisticalanalysis method. This means that this research uses activities in the form of datacollection, data processing and presentation. The technique of collecting research datais by conducting a test in the form of an objective test to choose one answer. The dataanalysis technique of this study used statistical data analysis, namely (1) normality test,(2) homogeneity test, (3) one sample t test. The results showed that the students' readingcomprehension ability of class VIII MTS Darul Hikmah Pekanbaru based on the resultsof the pre-test and post-test there were differences. The class average at the pretest was11.63 after the implementation of the constructivism approach in learning increased to16.77 at the post-test.Keywords: Reading Comprehension, Constructivism Model, Ability to Use ConstructivismModel